High-resilience TPU sole and preparation method thereof

By adding polystyrene particles, thermoplastic polyester elastomers, aramid fiber porous materials and carboxylated multi-wall carbon nanotubes to the TPU sole, and using supercritical carbon dioxide foaming and water vapor molding technology, the problem of weakening and deformation of TPU sole is solved, and a sole material with high resilience and morphological stability is achieved.

CN119798960APending Publication Date: 2025-04-11PUTIAN HANJIANG YIFENG FOOTWEAR IND CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510052745.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

After long-term use, the rebound resilience of existing TPU soles is weakened, which is prone to deformation problems and unstable structure.

Method used

Using TPU resin as the main material, polystyrene particles and thermoplastic polyester elastomer are added, combined with aramid fiber porous material and carboxylated multi-wall carbon nanotubes, and TPU soles with high resilience and morphological stability are prepared through supercritical carbon dioxide foaming and water vapor molding technology.

Benefits of technology

It significantly improves the elasticity and compressive strength of the TPU sole, reduces the compression permanent deformation rate, enhances the breathability and wear resistance of the material, and improves the overall performance of the sole.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240448620000071
    Figure BDA0005240448620000071
  • Figure BDA0005240448620000081
    Figure BDA0005240448620000081
  • Figure BDA0005240448620000111
    Figure BDA0005240448620000111
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials, and particularly discloses a high-resilience TPU shoe sole and a preparation method thereof. The high-resilience TPU sole is prepared from the following raw materials in parts by weight: 100 parts of TPU resin, 4 to 8 parts of carboxylated multi-walled carbon nanotubes, 15 to 20 parts of an aramid fiber porous material, 15 to 20 parts of polystyrene particles, 7 to 10 parts of a thermoplastic polyester elastomer, 0.1 to 0.5 part of an antioxidant, 0.5 to 2 parts of a nucleating agent, 1 to 2 parts of stearic acid and 0.1 to 0.5 part of a foam stabilizer. The TPU sole has the advantages of being high in rebound rate, small in permanent compression deformation, high in wear resistance and good in air permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and more specifically, to a high-resilience TPU sole and a preparation method thereof. Background Art

[0002] Thermoplastic polyurethane elastomer (TPU) is a type of elastomer that can be plasticized by heating. It has excellent properties such as high toughness, wear resistance, oil resistance and strong processability. Due to the above advantages, TPU can be used as a sole preparation material after foaming. The soles made from foamed TPU materials have the characteristics of light weight, durability, high resilience, etc., and are currently the most commonly used type of soles.

[0003] In the prior art, the Chinese invention patent document with application number CN2021109182429 discloses a high-resilience antibacterial TPU foam material and a preparation method thereof, which is composed of the following raw materials in parts by weight: 100 parts of TPU material; 10-20 parts of nylon elastomer; 1-2 parts of modified graphene / chitosan intercalated montmorillonite; 1-2 parts of stearic acid; 1-2 parts of cross-linking agent; 2-4 parts of blending agent; the antibacterial agent has strong high temperature resistance and is not prone to high temperature failure problems. It can also delay the release rate of the antibacterial agent, improve the dispersibility of the antibacterial agent in the matrix, and the rebound performance can reach more than 50%.

[0004] With respect to the above-mentioned related technologies, the inventors found that the addition of modified graphene / chitosan intercalated montmorillonite makes the foaming material have better resilience, but the structure of the sole material is not stable, and it is easy to have the problem of slow rebound and deformation during long-term use. Summary of the invention

[0005] In order to improve the resilience of the sole material while compressing and deforming the sole to improve its morphological stability, the present application provides a high-rebound TPU sole and a preparation method thereof.

[0006] In the first aspect, the present application provides a high-resilience TPU sole, which adopts the following technical solution: A high-resilience TPU sole comprises the following raw materials in parts by weight: 100 parts of TPU resin, 4-8 parts of carboxylated multi-walled carbon nanotubes, 15-20 parts of aramid fiber porous material, 15-20 parts of polystyrene particles, 7-10 parts of thermoplastic polyester elastomer, 0.1-0.5 parts of antioxidant, 0.5-2 parts of nucleating agent, 1-2 parts of stearic acid, and 0.1-0.5 parts of foam stabilizer.

[0007] By adopting the above technical scheme, TPU resin is used as the main material, and a certain amount of polystyrene particles and thermoplastic polyester elastomer are added to improve the resilience and compressive strength of the TPU sole. Thermoplastic polyester elastomer is a linear front-end copolymer containing polyester hard segment and aliphatic polyester or polyether soft segment, which has extremely high tensile strength, toughness and resilience. The addition of thermoplastic polyester elastomer can improve the viscoelasticity of the blend, thereby reducing the rupture, collapse or merging of bubbles during the foaming process, thereby preparing a TPU sole with uniform bubble morphology. Since the thermoplastic polyester elastomer contains a soft and hard block structure, it has a certain Crystallinity, and part of the crystalline area can be used as a physical cross-linking point. When external force is applied to the pores, part of the external force can be decomposed, thereby improving the toughness of the sole material, playing a certain buffering and shock-absorbing effect, and improving the resilience of the TPU sole. In addition, the thermoplastic polyester elastomer molecular chain contains soft and hard structures, which forms a crystalline area with certain physical cross-linking points, so it can obtain better recovery ability after compression deformation, reduce permanent compression deformation, and enhance its elastic recovery ability; the addition of polystyrene particles improves the tensile strength of the material, improves the foaming performance, enhances the resilience, and improves its tensile resistance.

[0008] The carboxylated multi-walled carbon nanotubes can be coated inside the TPU porous skeleton and dispersed evenly. The supporting effect of the carboxylated multi-walled carbon nanotubes on the porous material of the sole can improve the shape stability of the sole material after multiple compressions, reduce its compression permanent deformation rate, and improve the hydrophobicity of the sole and enhance its waterproof effect. Moreover, since the carbon nanotubes themselves have excellent air-conducting properties and can be more evenly dispersed in the TPU sole after carboxylation, the air permeability of the TPU sole can be improved to a certain extent. In addition, the carboxyl groups on the surface of the carboxylated multi-walled carbon nanotubes can interact with the functional groups in the TPU resin, thereby improving the compatibility and interfacial bonding strength of the multi-walled carbon nanotubes and the TPU resin, which is conducive to the uniform dispersion and stable existence of the multi-walled carbon nanotubes in the TPU resin, thereby having a positive effect on the air permeability, resilience, stretchability, etc.

[0009] TPU has the advantages of high tensile strength, large elongation, and low long-term compression permanent deformation rate. In addition, the foamed TPU has better resilience. Aramid fiber has excellent wear resistance and mechanical properties. Its addition to the sole material can indirectly improve the resilience of the TPU sole by enhancing the material structure and improving the overall rigidity. The high strength and rigidity of aramid fiber can enhance the compression resistance of the sole, thereby reducing deformation and improving the stability and durability of the sole. In addition, aramid porous material has good breathability, which can increase the breathability of the sole, reduce stuffiness and improve comfort.

[0010] Optionally, the preparation method of the aramid fiber porous material is as follows: Aramid fiber and polyimide fiber are mixed in a mass ratio of 1:2-3, deionized water is added to form a dispersion with a fiber concentration of 2-3wt%, sodium dodecyl sulfate is added, stirred evenly, pre-frozen and then freeze-dried, and dried at 105-110°C for 2-3h.

[0011] By adopting the above technical scheme, the polyimide fiber has a higher modulus and is suitable for use as a skeleton material for porous materials. Aramid fiber, as a high-performance fiber with high flexibility and high specific surface area, is often used as a reinforcing fiber. The surface of the polyimide fiber is smooth, and the fibers are irregularly interwoven to form a three-dimensional network structure. The aramid fiber is firmly bonded to the fiber interweaving, which strengthens the bonding between the fibers while maintaining the structure of the three-dimensional fiber network, so that the porous material has an extremely high porosity and good compression rebound performance, reducing the permanent compression deformation of the sole. Sodium dodecyl sulfate is used as a foaming agent to well disperse the polyimide fiber and the aramid fiber, and the aramid fiber can produce a coating and entanglement effect on the polyimide fiber network, so that it forms a porous material with a rich void structure; therefore, a water-based foam is used as a template to achieve good fiber dispersion and shaping of the pore structure, and to prepare a porous material with good air permeability and compression rebound performance.

[0012] Optionally, cellulose nanofibers are further added to the dispersion, and the added amount of the cellulose nanofibers is 3-7% of the total weight of the aramid fibers and the polyimide fibers.

[0013] By adopting the above technical scheme, cellulose nanofiber is a material with one-dimensional nanoscale, high specific surface area, rich surface chemical groups, high strength and high modulus and excellent thermal stability. In the preparation of porous materials, the foam has a richer void structure, which is beneficial to improving the gas circulation effect, thereby enhancing its air permeability; cellulose nanofibers and aramid fibers are wrapped on the surface of polyimide fibers to form a multi-size reinforced fiber skeleton structure, thereby giving the porous material a strong compression rebound performance; in addition, the nanoscale of cellulose nanofibers enables them to be closely arranged together to form a dense film, and the film-forming effect of cellulose nanofibers helps to improve the interface bonding between the fibers of each component, so cellulose nanofibers can be used as an adhesive to enhance the interface bonding force of polyimide fibers and aramid fibers, and at the same time form a high-strength, high-modulus film to further wrap and bond polyimide fibers and aramid fibers. The synergistic effect of multiple components is beneficial to improving the compressive strength of the material. When it is subjected to a large compressive load, it maintains a relatively stable structure, exhibits good compressible rebound elasticity, and reduces the permanent compression deformation rate. The rich chemical groups on the surface of cellulose nanofibers make them have high water absorption capacity when saturated with water. However, when excessive cellulose nanofibers are foamed, they can cooperate with aramid fibers to absorb a large amount of water, which inhibits the dynamic adsorption and release of sodium dodecyl sulfate at the gas-liquid interface, inhibits the formation of foam, affects the porosity in the porous material, and further affects the breathability of the sole.

[0014] Optionally, the aramid fiber is pretreated as follows: The aramid fiber is treated with alkali solution, washed to neutrality, added to a phosphoric acid solution with a concentration of 20-25wt%, refluxed at 40-50°C for 1-2h, washed with water to neutrality, and dried to obtain acidified aramid fiber; The acidified aramid fiber, DMAP and dichloromethane are mixed, chloroacetyl chloride and triethylamine are added, and the mixture is washed and dried after ice bathing overnight to obtain the modified aramid fiber, wherein the mass ratio of the acidified aramid fiber to the chloroacetyl chloride is 1:0.4-0.44; The modified aramid fiber, dodecylamine and DMF are reacted at 120-130° C. for 4-5 hours, washed and dried, and the mass ratio of the modified aramid fiber to dodecylamine is 1:0.8-1.

[0015] By adopting the above technical scheme, the aramid fiber is first treated with alkali solution to remove impurities on the surface of the aramid fiber, and then treated with phosphoric acid solution to generate hydroxyl groups and a small amount of carboxyl groups on the surface of the aramid fiber. Chloroacetyl chloride can interact with the aramid fiber containing hydroxyl groups after acidification, and the lipophilic monomer dodecylamine can be grafted onto the aramid fiber treated with chloroacetyl chloride through an amidation reaction, which can improve the dispersibility of the aramid fiber. The introduced dodecylamine is a long-chain molecule, which has a significant pulling effect on the TPU resin, can improve the tensile strength, and reduce the wear volume. At the same time, the aramid fiber grafted with dodecylamine has better compatibility with the TPU resin, making the material more uniform. The good pulling effect can reduce the replacement rate of the transfer film. At the same time, the good compatibility and mechanical strength can make the stress transfer effect more efficient, will not cause stress concentration in the base material, will not cause large-area damage, thereby improving the wear resistance of the sole.

[0016] Optionally, the carboxylated multi-walled carbon nanotubes are pretreated as follows: Dispersing carboxylated multi-walled carbon nanotubes in deionized water, filtering, and forming a carbon nanotube wet cake; Mixing polytetrafluoroethylene emulsion, mesoporous silica and ammonium carbonate to form a mixed emulsion; The mixed emulsion is evenly sprayed on the surface of the carbon nanotube wet cake and dried at 80-100° C. The mass ratio of the carbon nanotube wet cake to the mixed emulsion is 1:0.08-0.1.

[0017] By adopting the above technical scheme, the polytetrafluoroethylene emulsion bonds the mesoporous silica to the carbon nanotube wet cake, and after drying, the polytetrafluoroethylene solidifies to form an adhesive film with micropores, and the ammonium carbonate decomposes to form carbon dioxide and ammonia, thereby increasing the number of micropores on the polytetrafluoroethylene adhesive film, and the decomposition of ammonium carbonate can also make the mesoporous silica form through-going nanochannels, so that the air permeability of the carboxylated carbon nanotubes is improved. The sweat gas discharged from the foot is quickly discharged due to the capillary motion through the micropores because the water vapor particles are very small, while the external water is generally water droplets with larger particles. The surface tension of the water droplets makes it difficult to enter the sole material through the nanopores, thereby achieving the air permeability of the sole. Waterproof; polytetrafluoroethylene also has an excellent low friction coefficient, which can improve the wear resistance of carbon nanotubes, thereby enhancing the wear resistance of the sole; the attachment of mesoporous silica increases the roughness of the surface of carboxylated multi-walled carbon nanotubes, so that when force is applied, the actual contact area between the wear surface and the counter-wear surface is reduced, and the interaction force between the carboxylated multi-walled carbon nanotubes with increased surface roughness and the TPU resin matrix is ​​increased, which improves the interfacial adhesion, thereby reducing the wear rate and increasing the wear resistance; and after the polytetrafluoroethylene emulsion and mesoporous silica adhere to the surface of the carboxylated multi-walled carbon nanotubes, they can increase the shape stability of the multi-walled carbon nanotubes, improve the compression rebound effect of the TPU sole, and reduce the permanent compression deformation.

[0018] Optionally, the mass ratio of the polytetrafluoroethylene emulsion, mesoporous silica and ammonium carbonate is 1:0.1-0.2:0.03-0.05.

[0019] By adopting the above technical solution, the above amount of polytetrafluoroethylene emulsion and agglomerated silicon dioxide can form through nano-micropores on the carbon nanotubes, which is convenient for the discharge of foot sweat and increases the air permeability.

[0020] Optionally, the foam stabilizer is selected from at least one of propylene glycol ester, silicone oil, sulfonated fatty alcohol, sulfonated fatty acid, zinc nitrate and zinc oxide.

[0021] By adopting the above technical solution, the above foam stabilizer can maintain the stability of the pore wall, prevent the collapse or rupture of the pores caused by excessively fast gas generation rate or other factors, reduce the surface tension of the TPU foaming system, and help the gas to better disperse in the system and form fine bubbles, thereby obtaining a sole material with good resilience.

[0022] Optionally, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076 and antioxidant 168; the nucleating agent is selected from at least one of talc powder, mica powder, white carbon black and montmorillonite.

[0023] By adopting the above technical scheme, the antioxidant can prevent the sole from being oxidized and yellowing when exposed to oxygen environment, prolong the use performance and maintain the physical properties; the nucleating agent can accelerate the crystallization rate of TPU, increase the crystallization density, promote the refinement of grain size, shorten the molding cycle, improve production efficiency, and at the same time promote crystallization, improve mechanical properties, and enhance wear resistance.

[0024] In a second aspect, the present application provides a method for preparing a high-resilience TPU sole, using the following technical solution: A method for preparing a high-resilience TPU sole, comprising the following steps: The TPU resin is vacuum dried at 80-90°C, mixed with aramid fiber porous material, carboxylated multi-walled carbon nanotubes, polystyrene particles, antioxidant, nucleating agent, stearic acid and foam stabilizer, and extruded into granules to obtain composite particles; Supercritical carbon dioxide is introduced into the composite particles to a pressure of 12-15 MPa, the temperature is raised to 100-120° C., the pressure is maintained for 2-3 hours, and the pressure is released to obtain a foaming material; Water vapor is introduced into the foaming material, and the sole is obtained through steam forming, molding, cooling and demoulding.

[0025] By adopting the above technical scheme, the raw materials are melt-blended and then granulated, and then supercritically foamed to obtain a microporous structure similar to popcorn, thereby improving the lightweight of the product, while obtaining excellent elasticity and rebound effects, good shockproof effect, and significant wear resistance. Then, water vapor molding is used to melt and bond the various foaming materials to obtain a stable sole.

[0026] Optionally, the steam molding temperature is 130-150° C., the molding time is 150-190 s, and the molding pressure is 0.3-0.5 MPa.

[0027] By adopting the above technical solution, appropriate steam temperature, pressure and time can make the foaming material fully melt and bond, while avoiding excessive temperature that may cause material degradation or burning, thereby forming a sole with excellent resilience and wear resistance.

[0028] In summary, this application has the following beneficial effects: 1. Since the present application adopts TPU resin as the matrix, polystyrene particles and thermoplastic polyester elastomer are added to improve the foaming uniformity and resilience of the TPU sole and reduce the compression permanent deformation rate. In addition, aramid fiber porous material and carboxylated multi-walled carbon nanotubes are used to further improve the compression deformation resistance of the TPU sole and improve the tensile strength, wear resistance and breathability of the material.

[0029] 2. In the present application, aramid fiber and polyimide fiber are preferably used to prepare porous materials with sodium dodecyl sulfate as a foaming agent. The fibers overlap each other to form a network structure with extremely high porosity, good compression resilience and good air permeability, thereby improving the compression rebound effect and air permeability and anti-stuffiness effect of the sole.

[0030] 3. In the present application, carboxylated multi-walled carbon nanotubes are treated with polytetrafluoroethylene emulsion, mesoporous silica and ammonium carbonate. Mesoporous silica is loaded on carbon nanotubes using polytetrafluoroethylene emulsion. The pore-forming effect of ammonium carbonate increases the nanopores on the surface of polytetrafluoroethylene emulsion and mesoporous silica, thereby enhancing the improvement of the air permeability of the sole by the carboxylated multi-walled carbon nanotubes, while further enhancing the wear resistance and reducing the compression set. DETAILED DESCRIPTION

[0031] The following examples further illustrate the present application in detail.

[0032] Preparation Examples 1-9 of Aramid Fiber Porous Materials In the preparation example, the polyimide fiber is 6 mm long and is selected from Hubei Tengdi New Materials Co., Ltd. with the product number TD204720. The aramid fiber is selected from Shenzhen Guosen Linghang Technology Co., Ltd. with the product number 800D03MM and the length is 3 mm. The cellulose nanofiber is selected from Northern Century (Jiangsu) Cellulose Materials with a density of 1.6 g / cm 3 .

[0033] Preparation Example 1: 1 g of aramid fiber and polyimide fiber are mixed in a mass ratio of 1:3, deionized water is added to prepare a dispersion with a fiber concentration of 2 wt%, cellulose nanofibers are added to the dispersion, and then 0.12 g of sodium dodecyl sulfate is added. After stirring evenly, the mixture is pre-frozen at -60°C for 30 min, freeze-dried at -70°C for 24 h, and dried at 110°C for 2 h. The amount of cellulose nanofiber added is 7% of the total weight of the aramid fiber and polyimide fiber.

[0034] Preparation Example 2: 1 g of aramid fiber and polyimide fiber are mixed in a mass ratio of 1:2, deionized water is added to prepare a dispersion with a fiber concentration of 3 wt%, cellulose nanofibers are added to the dispersion, and then 0.12 g of sodium dodecyl sulfate is added. After stirring evenly, the mixture is pre-frozen at -60°C for 30 min, freeze-dried at -70°C for 24 h, and dried at 105°C for 3 h. The amount of cellulose nanofiber added is 3% of the total weight of the aramid fiber and polyimide fiber.

[0035] Preparation Example 2: The difference from Preparation Example 1 is that no cellulose nanofibers are added.

[0036] Preparation Example 4: The difference from Preparation Example 1 is that cellulose nanofibers are not added, and aramid fibers are used in an equal amount to replace polyimide fibers. The specific method is: 1 g of aramid fibers are dispersed in deionized water to form a dispersion with a concentration of 2 wt%, 0.12 g of sodium dodecyl sulfate is added, and the mixture is pre-frozen at -60°C for 30 min, then freeze-dried at -70°C for 24 h, and dried at 110°C for 2 h.

[0037] Preparation Example 5: The difference from Preparation Example 1 is that the aramid fiber is first pretreated as follows: the aramid fiber is added to a 15wt% sodium hydroxide solution, immersed at 80°C for 4h, filtered, washed to neutrality, added to a 25wt% phosphoric acid solution, refluxed at 40°C for 2h, washed with water to neutrality, and dried to obtain acidified aramid fiber; 2.58 g of acidified aramid fiber was mixed with 0.01 g of DMAP and 30 ml of dichloromethane, and 1.12 g of chloroacetyl chloride and 0.05 g of triethylamine were added, and the mixture was washed and dried after ice bathing overnight to obtain modified aramid fiber; 3 g of modified aramid fiber, 3 g of dodecylamine and 30 ml of DMF were mixed evenly, reacted at 120° C. for 5 h, washed and dried.

[0038] Preparation Example 6: The difference from Preparation Example 1 is that the aramid fiber is first pretreated as follows: the aramid fiber is added to a 13wt% sodium hydroxide solution, immersed at 90°C for 3h, filtered, washed to neutrality, added to a 20wt% phosphoric acid solution, refluxed at 50°C for 1h, washed with water to neutrality, and dried to obtain acidified aramid fiber; 2.58 g of acidified aramid fiber was mixed with 0.01 g of DMAP and 30 ml of dichloromethane, and 1.032 g of chloroacetyl chloride and 0.05 g of triethylamine were added, and the mixture was washed and dried after ice bathing overnight to obtain modified aramid fiber; 3 g of modified aramid fiber, 2.4 g of dodecylamine and 30 ml of DMF were mixed evenly, reacted at 130° C. for 4 h, washed and dried.

[0039] Preparation Example 7: The difference from Preparation Example 5 is that when pre-treating the aramid fiber, the aramid fiber is impregnated with an alkali solution and a phosphoric acid solution, 2.58 g of the aramid fiber is directly mixed with 0.01 g of DMAP and 30 ml of dichloromethane, 1.12 g of chloroacetyl chloride and 0.05 g of triethylamine are added, and the fiber is washed and dried after ice bathing overnight to obtain a modified aramid fiber; 3 g of modified aramid fiber, 3 g of dodecylamine and 30 ml of DMF were mixed evenly, reacted at 120° C. for 5 h, washed and dried.

[0040] Preparation Example 8: The difference from Preparation Example 5 is that no dodecylamine is added, 2.58 g of acidified aramid fiber is mixed with 0.01 g of DMAP and 30 ml of dichloromethane, 1.12 g of chloroacetyl chloride and 0.05 g of triethylamine are added, and the mixture is washed and dried after ice bathing overnight.

[0041] Preparation Example 9: The difference from Preparation Example 5 is that chloroacetyl chloride is not added. 3 g of acidified aramid fiber, 3 g of dodecylamine and 30 ml of DMF are mixed evenly, reacted at 120° C. for 5 h, washed and dried. Example

[0042] Example 1: A high-resilience TPU sole, the raw material dosage is shown in Table 1, the TPU resin is selected from Bayer, Germany, the model is 9385A, and the density is 1.12g / cm 3, Shore hardness is 35D; carboxylated multi-walled carbon nanotubes are selected from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with item number 100233, serial number XFM03, length 10-30 μm, diameter 5-15 nm, inner diameter 2-5 nm; aramid fiber porous material is prepared according to Preparation Example 1; polystyrene particles are selected from Qingdao Mattel Plastics, model PG-383, density 1.04 g / cm 3 Thermoplastic polyester elastomer is selected from DuPont, USA, model 3078, density 1.07g / cm 3 , Shore hardness is 30D, nucleating agent is talcum powder, particle size is 125 mesh; foam stabilizer is silicone oil; antioxidant is antioxidant 1010, selected from Jihong Chemical.

[0043] The method for preparing the high-resilience TPU sole comprises the following steps: S1, drying the TPU resin under vacuum at 80° C. for 4 h, mixing it with aramid fiber porous material, carboxylated multi-walled carbon nanotubes, polystyrene particles, thermoplastic polyester elastomer, antioxidant, nucleating agent, stearic acid and foam stabilizer, extruding and granulating to obtain composite particles, the temperatures of each zone of the extruder being: 170° C., 175° C., 175° C., 175° C., 180° C.; Supercritical carbon dioxide is introduced into the composite particles to a pressure of 12 MPa, the temperature is raised to 120°C, the pressure is maintained for 2 hours, and the pressure is released to obtain a foaming material; water vapor is introduced into the foaming material, and the sole is obtained through steam molding, compression molding, cooling, and demolding. The steam molding temperature is 130°C, the molding time is 190s, the molding pressure is 0.3MPa, and the compression molding temperature is 180°C, the time is 30s, and the pressure is 20MPa.

[0044] Table 1 Amount of raw materials used for high resilience TPU soles in Examples 1-3 Example 2: A high-resilience TPU sole, the raw material dosage is shown in Table 1, the TPU resin is selected from Bayer, Germany, the model is 9385A, and the density is 1.12g / cm 3 , Shore hardness is 35D; carboxylated multi-walled carbon nanotubes are selected from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with item number 100233, serial number XFM03, length 10-30 μm, diameter 5-15 nm, inner diameter 2-5 nm; aramid fiber porous material is prepared by Preparation Example 2; polystyrene particles are selected from Qingdao Mattel Plastics, model PG-383, density 1.04 g / cm 3 Thermoplastic polyester elastomer is selected from DuPont, USA, model 3078, density 1.07g / cm 3, Shore hardness is 30D, the nucleating agent is white carbon black, selected from Jiangsu Tianxing New Materials, item number TSP-L12; the foam stabilizer is zinc oxide; the antioxidant is antioxidant 1076, selected from BASF.

[0045] The method for preparing the high-resilience TPU sole comprises the following steps: S1, vacuum drying the TPU resin at 90°C for 3h, mixing it with aramid fiber porous material, carboxylated multi-walled carbon nanotubes, polystyrene particles, thermoplastic polyester elastomer, antioxidant, nucleating agent, stearic acid and foam stabilizer, extruding and granulating to obtain composite particles, the temperatures of each zone of the extruder are: 170°C, 175°C, 175°C, 175°C, 180°C; Supercritical carbon dioxide is introduced into the composite particles to a pressure of 15 MPa, the temperature is raised to 100°C, the pressure is maintained for 3 hours, and the pressure is released to obtain a foaming material; water vapor is introduced into the foaming material, and the sole is obtained through steam molding, compression molding, cooling, and demolding. The steam molding temperature is 150°C, the molding time is 150s, the molding pressure is 0.5MPa, and the compression molding temperature is 180°C, the time is 30s, and the pressure is 20MPa.

[0046] Example 3: A high-resilience TPU sole, the raw material dosage is shown in Table 1, the TPU resin is selected from Bayer, Germany, the model is 9385A, and the density is 1.12g / cm 3 , Shore hardness is 35D; carboxylated multi-walled carbon nanotubes are selected from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with item number 100233, serial number XFM03, length 10-30 μm, diameter 5-15 nm, inner diameter 2-5 nm; aramid fiber porous material is prepared by Preparation Example 1; thermoplastic polyester elastomer is selected from DuPont, USA, model 3078, density 1.07 g / cm 3 , Shore hardness is 30D, polystyrene particles are selected from Qingdao Mattel Plastics, model PG-383, density 1.04g / cm 3 ; The nucleating agent is mica powder with a particle size of 1250 mesh; the foam stabilizer is propylene glycol ester; the antioxidant is antioxidant 168, selected from BASF.

[0047] The method for preparing the high-resilience TPU sole comprises the following steps: S1, vacuum drying the TPU resin at 80°C for 3h, mixing it with aramid fiber porous material, carboxylated multi-walled carbon nanotubes, polystyrene particles, thermoplastic polyester elastomer, antioxidant, nucleating agent, stearic acid and foam stabilizer, extruding and granulating to obtain composite particles, the temperatures of each zone of the extruder are: 170°C, 175°C, 175°C, 175°C, 180°C; Supercritical carbon dioxide was introduced into the composite particles to a pressure of 14 MPa, the temperature was raised to 110° C., the pressure was maintained for 2.5 hours, and the pressure was released to obtain a foaming material; Water vapor is introduced into the foaming material, and the sole is obtained through steam molding, molding, cooling and demolding. The steam molding temperature is 140°C, the molding time is 170s, the molding pressure is 0.4MPa, and the molding temperature is 180°C, the time is 30s, and the pressure is 20MPa.

[0048] Example 4: A high-resilience TPU sole, which is different from Example 1 in that the aramid fiber porous material is made from Preparation Example 3.

[0049] Example 5: A high-resilience TPU sole. The difference from Example 1 is that the aramid fiber porous material is made from Preparation Example 4.

[0050] Example 6: A high-resilience TPU sole, which is different from Example 1 in that the aramid fiber porous material is made from Preparation Example 5.

[0051] Example 7: A high-resilience TPU sole, which is different from Example 1 in that the aramid fiber porous material is made from Preparation Example 6.

[0052] Example 8: A high-resilience TPU sole, which is different from Example 6 in that the aramid fiber porous material is made from Preparation Example 7.

[0053] Example 9: A high-resilience TPU sole. The difference from Example 6 is that the aramid fiber porous material is made from Preparation Example 8.

[0054] Example 10: A high-resilience TPU sole. The difference from Example 6 is that the aramid fiber porous material is made from Preparation Example 9.

[0055] Example 11: A high-resilience TPU sole, which is different from Example 6 in that the carboxylated multi-walled carbon nanotubes are pretreated as follows: Disperse 1 g of carboxylated multi-walled carbon nanotubes into 20 g of deionized water and vacuum filter to form a carbon nanotube wet cake; 10g of polytetrafluoroethylene emulsion, 2g of mesoporous silica and 0.5g of ammonium carbonate were mixed to form a mixed emulsion, the polytetrafluoroethylene emulsion was selected from Shanghai Yumingshen Plastic Chemical Co., Ltd., with a product number of JF-4DCT, and the mesoporous silica was selected from Wuhu Xinda New Materials, with a model number of XD-S05J; The mixed emulsion was uniformly sprayed on the surface of the carbon nanotube wet cake and dried at 100° C. The mass ratio of the carbon nanotube wet cake to the mixed emulsion was 1:0.1.

[0056] Example 12: A high-resilience TPU sole, which is different from Example 6 in that the carboxylated multi-walled carbon nanotubes are pretreated as follows: Disperse 1 g of carboxylated multi-walled carbon nanotubes into 20 g of deionized water and vacuum filter to form a carbon nanotube wet cake; 10g of polytetrafluoroethylene emulsion, 1g of mesoporous silica and 0.3g of ammonium carbonate were mixed to form a mixed emulsion, the polytetrafluoroethylene emulsion was selected from Shanghai Yumingshen Plastic Chemical Co., Ltd., with a product number of JF-4DCT, and the mesoporous silica was selected from Wuhu Xinda New Materials, with a model number of XD-S05J; The mixed emulsion was uniformly sprayed on the surface of the carbon nanotube wet cake and dried at 80° C. The mass ratio of the carbon nanotube wet cake to the mixed emulsion was 1:0.08.

[0057] Example 13: A high-resilience TPU sole, which is different from Example 11 in that ammonium carbonate is not added during the pretreatment of the carboxylated multi-walled carbon nanotubes.

[0058] Example 14: A high-resilience TPU sole, which differs from Example 11 in that, when pretreating the carboxylated multi-walled carbon nanotubes, an equal amount of deionized water is used to replace the polytetrafluoroethylene emulsion.

[0059] Example 15: A high-resilience TPU sole, which is different from Example 11 in that mesoporous silica and ammonium carbonate are not added during the pretreatment of carboxylated multi-walled carbon nanotubes.

[0060] Comparative Example Comparative Example 1: A high-resilience TPU sole, which differs from Example 1 in that no aramid fiber porous material is added.

[0061] Comparative Example 2: A high-resilience TPU sole. The difference from Example 1 is that an equal amount of non-carboxylated multi-walled carbon nanotubes is used to replace the carboxylated multi-walled carbon nanotubes. The multi-walled carbon nanotubes are selected from Shenzhen Guosen Linghang Technology Co., Ltd., model GS7758258, and item number 008.

[0062] Comparative Example 3: A high-resilience TPU sole, which differs from Example 1 in that carboxylated multi-walled carbon nanotubes are not added.

[0063] Comparative Example 4: A high-resilience TPU sole, which differs from Example 1 in that an equal amount of carboxylated multi-walled carbon nanotubes is used to replace the aramid fiber porous material.

[0064] Performance testing The TPU soles were prepared according to the methods in the examples and comparative examples, and the performance tests were performed according to the following methods. The test results are recorded in Table 2.

[0065] 1. Rebound rate: Tested in accordance with GB / T6670-2008 "Determination of rebound properties of soft foam polymer materials by falling ball method".

[0066] 2. Compression permanent deformation: Use parallel plate fixture to test in accordance with GB / T6669-2008 "Determination of compression permanent deformation of soft foam polymer materials".

[0067] 3. Tensile strength: Tested in accordance with GB / T6344-2008 "Determination of tensile strength and elongation at break of soft foam polymer materials".

[0068] 4. Air permeability: Use the SYSTESTER vulcanized rubber air permeability tester to test the air permeability rate of the sole.

[0069] 5. Wear resistance: Test in accordance with GB / T9867-2009 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrasion machine)".

[0070] Table 2 Performance test results of high rebound TPU sole Combining Examples 1-3 and the data in Table 2, it can be seen that the aramid fiber porous materials prepared in Preparation Example 1 and Preparation Example 2 are respectively used in Examples 1-3, and a certain amount of polystyrene particles and thermoplastic polyester elastomer are combined. The TPU soles prepared in this way have a high rebound rate, small compression permanent deformation, good shape stability, high tensile strength, strong mechanical properties, small wear, excellent wear resistance, and good air permeability, avoiding stuffiness when wearing, and high comfort.

[0071] In Example 4, the aramid fiber porous material prepared in Preparation Example 3 was used. Compared with Example 1, cellulose nanofibers were not added when preparing the aramid fiber porous material. The data in Table 2 showed that the resilience and wear of the TPU sole prepared in Example 4 were slightly reduced, the compression permanent deformation was increased, and the air permeability was significantly reduced, indicating that the addition of cellulose nanofibers can improve the porosity of the aramid fiber porous material, enhance the air permeability, improve the compression rebound effect, and reduce the compression permanent deformation.

[0072] Example 5 Compared with Example 1, the aramid fiber porous material prepared in Preparation Example 4 is used, to which cellulose nanofibers and polyimide fibers are not added, and only aramid fibers are used to prepare the porous material. It can be seen that the resilience of the TPU sole is reduced, the tensile strength and the wear amount are significantly reduced, the air permeability is deteriorated, and the compression permanent deformation is increased.

[0073] Compared with Example 1, Examples 6 and 7 respectively use the aramid fiber porous materials prepared in Preparation Examples 5 and 6. In Preparation Examples 5 and 6, the aramid fibers are pretreated with phosphoric acid solution, chloroacetyl chloride, dodecylamine, etc. It can be seen from the data in Table 2 that the tensile strength of the TPU soles prepared in Examples 6 and 7 is further increased, and the wear amount is significantly reduced, indicating that the aramid fiber porous material prepared after pretreatment of the aramid fibers can significantly improve the tensile and wear resistance of the soles.

[0074] In Example 8, the aramid fiber porous material was prepared using Preparation Example 7. Compared with Preparation Example 5 in Example 6, the aramid fiber was not impregnated with alkali solution and phosphoric acid solution. In Example 9, the aramid fiber porous material prepared in Preparation Example 8 was used. Compared with Preparation Example 5, dodecanoic acid was not added in Preparation Example 8, and only the acidified aramid fiber was mixed with chloroacetyl chloride and the like. In Example 10, the aramid fiber porous material prepared in Preparation Example 9 was used. Compared with Preparation Example 5, chloroacetyl chloride was not added. It can be seen from the data in Table 2 that the TPU soles prepared in Examples 8-10 have decreased tensile strength, decreased wear, and weakened tensile and wear resistance compared with Example 6.

[0075] Compared with Example 6, Examples 11 and 12 also use polytetrafluoroethylene emulsion, mesoporous silica and ammonium carbonate to pretreat the carboxylated multi-walled carbon nanotubes. It can be seen from the data in Table 2 that after pretreatment, the carboxylated multi-walled carbon nanotubes can effectively improve the tensile strength and wear resistance of the TPU sole, increase the air permeability, and reduce the permanent compression deformation.

[0076] Compared with Example 11, no ammonium carbonate was added during the pretreatment of carboxylated multi-walled carbon nanotubes in Example 13. As can be seen from the data in Table 2, the air permeability of the TPU sole prepared in Example 13 decreased significantly, and the other properties did not change significantly.

[0077] In Example 14, compared with Example 11, deionized water is used to replace the polytetrafluoroethylene emulsion, and the tensile strength of the prepared TPU sole decreases, the wear resistance weakens, and the air permeability decreases slightly.

[0078] In Example 15, when pretreating the carboxylated multi-walled carbon nanotubes, no mesoporous silica and ammonium carbonate were added, and the wear resistance of the TPU soles prepared thereby decreased significantly, and the air permeability decreased, and the tensile strength weakened.

[0079] Compared with Example 1, Comparative Example 1 does not add aramid fiber porous material. It can be seen that the air permeability of the TPU sole decreases, the wear resistance weakens, the tensile strength decreases, and various performances are changed. It can be seen that the aramid fiber porous material can effectively reduce the compression deformation of the sole, while increasing the resilience, and improving the wear resistance and tear resistance.

[0080] Comparative Example 2 uses multi-walled carbon nanotubes instead of carboxylated multi-walled carbon nanotubes, and Comparative Example 3 does not add carboxylated multi-walled carbon nanotubes. It can be seen that the performance of the TPU soles prepared in Comparative Examples 2 and 3 are reduced, and the reduction in Comparative Example 3 is more significant.

[0081] In Comparative Example 4, an equal amount of carboxylated multi-walled carbon nanotubes is used to replace the aramid fiber porous material. It can be seen that the resilience and compression deformation of the TPU sole prepared in Comparative Example 4 are not as good as those in Example 1.

[0082] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-resilience TPU sole, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of TPU resin, 4-8 parts of carboxylated multi-walled carbon nanotubes, 15-20 parts of aramid fiber porous material, 15-20 parts of polystyrene particles, 7-10 parts of thermoplastic polyester elastomer, 0.1-0.5 parts of antioxidant, 0.5-2 parts of nucleating agent, 1-2 parts of stearic acid, and 0.1-0.5 parts of foam stabilizer.

2. The high-resilience TPU sole according to claim 1, characterized in that: The preparation method of the aramid fiber porous material is as follows: Aramid fiber and polyimide fiber are mixed in a mass ratio of 1:2-3, deionized water is added to form a dispersion with a fiber concentration of 2-3wt%, sodium dodecyl sulfate is added, stirred evenly, pre-frozen and then freeze-dried, and dried at 105-110°C for 2-3h.

3. The high-resilience TPU sole according to claim 2, characterized in that: Cellulose nanofibers are also added to the dispersion, and the added amount of the cellulose nanofibers is 3-7% of the total weight of the aramid fibers and the polyimide fibers.

4. The high-resilience TPU sole according to claim 3, characterized in that: The aramid fiber is pretreated as follows: The aramid fiber is treated with alkali solution, washed to neutrality, added to a phosphoric acid solution with a concentration of 20-25wt%, refluxed at 40-50°C for 1-2h, washed with water to neutrality, and dried to obtain the acidified aramid fiber; The acidified aramid fiber, DMAP and dichloromethane are mixed, chloroacetyl chloride and triethylamine are added, and the mixture is washed and dried after ice bathing overnight to obtain the modified aramid fiber, wherein the mass ratio of the acidified aramid fiber to the chloroacetyl chloride is 1:0.4-0.44; The modified aramid fiber, dodecylamine and DMF are reacted at 120-130° C. for 4-5 hours, washed and dried, and the mass ratio of the modified aramid fiber to dodecylamine is 1:0.8-1.

5. The high-resilience TPU sole according to claim 1, characterized in that: The carboxylated multi-walled carbon nanotubes are pretreated as follows: Dispersing carboxylated multi-walled carbon nanotubes in deionized water, filtering, and forming a carbon nanotube wet cake; Mixing polytetrafluoroethylene emulsion, mesoporous silica and ammonium carbonate to form a mixed emulsion; The mixed emulsion is evenly sprayed on the surface of the carbon nanotube wet cake and dried at 80-100° C. The mass ratio of the carbon nanotube wet cake to the mixed emulsion is 1:0.08-0.

1.

6. The high-resilience TPU sole according to claim 5, characterized in that: The mass ratio of the polytetrafluoroethylene emulsion, mesoporous silica and ammonium carbonate is 1:0.1-0.2:0.03-0.

05.

7. The high-resilience TPU sole according to claim 1, characterized in that: The foam stabilizer is selected from at least one of propylene glycol ester, silicone oil, sulfonated fatty alcohol, sulfonated fatty acid, zinc nitrate and zinc oxide.

8. The high-resilience TPU sole according to claim 1, characterized in that: The antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076 and antioxidant 168; The nucleating agent is selected from at least one of talc powder, mica powder, white carbon black and montmorillonite.

9. The method for preparing the high-resilience TPU sole according to any one of claims 1 to 8, characterized in that: The following steps are involved: The TPU resin is vacuum dried at 80-90°C, mixed with aramid fiber porous material, carboxylated multi-walled carbon nanotubes, polystyrene particles, thermoplastic polyester elastomer, antioxidant, nucleating agent, stearic acid and foam stabilizer, and extruded into granules to obtain composite particles; Supercritical carbon dioxide is introduced into the composite particles to a pressure of 12-15 MPa, the temperature is raised to 100-120° C., the pressure is maintained for 2-3 hours, and the pressure is released to obtain a foaming material; Water vapor is introduced into the foaming material, and the sole is obtained through steam forming, molding, cooling and demoulding.

10. The method for preparing a high-resilience TPU sole according to claim 9, characterized in that: The steam molding temperature is 130-150° C., the molding time is 150-190 s, and the molding pressure is 0.3-0.5 MPa.

Citation Information

Cited By

  • Silicone rubber anti-skid material for food shoes and preparation method of silicone rubber anti-skid material

    CN122080646A